2002
DOI: 10.2337/diabetes.51.6.1825
|View full text |Cite
|
Sign up to set email alerts
|

The Composition of Dietary Fat Directly Influences Glucose-Stimulated Insulin Secretion in Rats

Abstract: Acute elevations of plasma free fatty acid (FFA) levels augment glucose-stimulated insulin secretion (GSIS). Prolonged elevations of FFA levels reportedly impair GSIS, but no one has previously compared GSIS after prolonged exposure to saturated or unsaturated fat. Because the GSIS of rats consuming Lard diets consistently exceeded that of the Soy group, we also assessed responses after 48-h infusions of lard or soy oil. Again, lard oil exhibited greater insulinotropic potency. These data indicate that prolong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
94
3
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(106 citation statements)
references
References 79 publications
7
94
3
2
Order By: Relevance
“…The appearance of the long-chain C22:1 fatty acid and the impairment of insulin secretion were consistent with previous studies reporting that the increase of the number of carbons has a negative effect on insulin release by increasing β-cell KATP channel activity and inducing the uncoupling of β-cell oxidative phosphorylation [7,16]. Other studies show that saturated fatty acids are associated with a higher risk of type 2 diabetes [18,20,24]. In our study, the decrease in saturated fatty acids observed in islets isolated from treated W rats may represent an attempt of animals to circumvent the β-cell secretory deficiency.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The appearance of the long-chain C22:1 fatty acid and the impairment of insulin secretion were consistent with previous studies reporting that the increase of the number of carbons has a negative effect on insulin release by increasing β-cell KATP channel activity and inducing the uncoupling of β-cell oxidative phosphorylation [7,16]. Other studies show that saturated fatty acids are associated with a higher risk of type 2 diabetes [18,20,24]. In our study, the decrease in saturated fatty acids observed in islets isolated from treated W rats may represent an attempt of animals to circumvent the β-cell secretory deficiency.…”
Section: Discussionsupporting
confidence: 91%
“…Accumulating evidence suggests that chain length, spatial conformation and degree of saturation of FFAs profoundly influence the insulinotropic potency and the stimulation of KATP channel activity [7,16,[18][19][20]. Studies focussed on fatty acids chain length reported that the increase of the number of carbons has a negative effect on insulin release by increasing β-cell KATP channel activity and induces uncoupling of β-cell oxidative phosphorylation [7,16,18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, no differences in insulin responses were found after meals [39,40] or longterm diets [41], which were high in monounsaturated or saturated fatty acids. Some studies have reported greater stimulation of insulin secretion after diets high in saturated fatty acids in subjects with Type II diabetes [42] and normal rats [43] but others have reported a more pronounced effect with polyunsaturated fatty acids [44]. A comparable pattern of glucose-stimulated insulin response to that observed in our study was seen when similar oils were given as a mixed test meal followed by a glucose drink [45].…”
Section: Discussionsupporting
confidence: 81%